Fish Diversity in Extreme Flood in Epie Creek, Bayelsa State, Niger delta - Sabina Alatari Ngodigha (Formosa Journal of Science and Technology, 2023)
Floods have been of great concern in the Niger Delta in the recent years, precipitating this study. The research was conducted to investigate diversity of fish species in the October 2022 extreme flood in the Niger Delta. Samples were collected randomly from landings of artisanal fishers in five sample locations, sorted and identified to species level. Diversity was estimated using Shannon-Wiener's diversity H' and Simpson's diversity D indices. Richness R, Evenness E and Similarity between stations were analyzed accordingly. From the results, R was from 4.255-4.535, E was 0.789 to 0.899 and H’ 1.734-1.974. Simpson’s index D was between 0.162 and 0.226, while Simpson’s index of diversity 1-D was from 0.774 to 0.838. Highest similarity value between stations was 0.286. Results from the study indicate the creek experienced a stable system during the October 2022 flood.